2011
DOI: 10.1016/j.molcel.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Sub1 and RPA Associate with RNA Polymerase II at Different Stages of Transcription

Abstract: Summary Single stranded DNA binding proteins play many roles in nucleic acid metabolism, but their importance during transcription remains unclear. Quantitative proteomic analysis of RNA polymerase II (RNApII) pre-initiation complexes (PICs) identified Sub1 and the Replication Protein A complex (RPA), both of which bind single-stranded DNA (ssDNA). Sub1, homolog of mammalian coactivator PC4, exhibits strong genetic interactions with factors necessary for promoter melting. Sub1 localizes near the transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
115
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(128 citation statements)
references
References 75 publications
(128 reference statements)
10
115
1
1
Order By: Relevance
“…A recent study in yeast reported the RPa complex composed of RPa1, -2, and -3, which we demonstrate associates with Sox2 (Fig. 6), plays an important role during transcriptional elongation (34). Additionally, another report demonstrated that the DNA repair XPC nucleotide excision repair complex, composed of Xpc, Rad23b, and Cetn2, is necessary for Sox2 and Oct4 to activate the expression of the Nanog promoter (35).…”
Section: Discussionsupporting
confidence: 59%
“…A recent study in yeast reported the RPa complex composed of RPa1, -2, and -3, which we demonstrate associates with Sox2 (Fig. 6), plays an important role during transcriptional elongation (34). Additionally, another report demonstrated that the DNA repair XPC nucleotide excision repair complex, composed of Xpc, Rad23b, and Cetn2, is necessary for Sox2 and Oct4 to activate the expression of the Nanog promoter (35).…”
Section: Discussionsupporting
confidence: 59%
“…We hypothesize that RNA polymerase II promotes the recruitment of the repair factors to the DSB site at the active gene (and hence stimulates DSB repair), analogous to the fact that RNA polymerase II facilitates the recruitment of TC-NER-specific factor Rad26p to the DNA lesion at the active gene to promote NER (25). In support of this hypothesis, a recent study (57) implicated the interaction of RNA polymerase II with RPA (replication protein A complex), which is involved in DSB repair. Further, the INO80 chromatin remodeling complex that promotes DSB repair is recruited to the gene in a transcription-dependent manner (58,59).…”
Section: Induction Of Dsbs At the Highly Active Adh1 And Nearlymentioning
confidence: 76%
“…Recent studies have shown that two proteins linked to termination are enriched in pre-initiation complexes assembled in vitro (33,34). One is Sub1, which is thought to repress the termination activity of cleavage factor IA (35), and thus unlikely to promote release in our assay.…”
Section: Discussionmentioning
confidence: 94%